Assessing Pulmonary Embolism in the Emergency Department: The Role of the YEARS Algorithm. - Davis, Philip; Alvarez, Marlen (Advanced Emergency Nursing Journal)
Chest pain and shortness of breath are frequent reasons for visits to the emergency department and may indicate life-threatening conditions – a cannot miss being pulmonary embolism. To aid in the diagnosis and exclusion of PE, several clinical decision support tools are available including the Wells score, PERC, Geneva score and the YEARS algorithm. The Research to Practice column critically evaluates recent studies and translates their findings, within the context of a clinical case, into actionable changes for emergency care. This article examines the findings of a recent systemic review and meta-analysis that evaluated the diagnostic accuracy of YEARS algorithm in identifying suspected PE, with a particular focus on minimizing the use of unnecessary advanced imaging.